2009
DOI: 10.1590/s0102-311x2009000700018
|View full text |Cite
|
Sign up to set email alerts
|

User satisfaction with pharmacy services in the Brazilian National STD/AIDS Program: validity and reliability issues

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…Despite the lack of other similar studies to allow direct comparison of these findings, our results are in accordance to other authors, that showed that the higher the waiting time (actual or perceived), the lower the level of the users' satisfaction [28][29][30][31] . Problems regarding dispensary space are not uncommon in Brazil, as highlighted by other authors 32,33 and one important recommendation for good pharmaceutical services is that dispensary space needs to be optimally designed to ensure efficient processing of prescriptions 34 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite the lack of other similar studies to allow direct comparison of these findings, our results are in accordance to other authors, that showed that the higher the waiting time (actual or perceived), the lower the level of the users' satisfaction [28][29][30][31] . Problems regarding dispensary space are not uncommon in Brazil, as highlighted by other authors 32,33 and one important recommendation for good pharmaceutical services is that dispensary space needs to be optimally designed to ensure efficient processing of prescriptions 34 .…”
Section: Discussionsupporting
confidence: 91%
“…This information can be corroborated by an official report from the Minas Gerais Court of Auditors that concluded that all the pharmaceutical services at the State were in high risk of destocking due to poor management practices 37 . Despite the importance of all dimensions of access to medicines, availability showed the strongest association with users satisfaction 30,38 . In this study we also evaluated the PHCPS' dispensing practices, since dispensing medicines is one of the core activities of these services 5 .…”
Section: Discussionmentioning
confidence: 99%